Efficacy and safety of hypoglycemic agents on gestational diabetes mellitus in women: A Bayesian network analysis of randomized controlled trials - Wang, Ting; Jing, Yingyu; Guo, Haonan; Xu, Jing; Wang, Man; Huang, Lili; Chen, Huan; Cui, Wei; Song, Lin; Liu, Xiang; Sun, Bo; Wang, Ning (Frontiers in Public Health, 2022)
Objective: To compare the efficacy and safety of metformin, glyburide, and insulin for GDM women, conduct a subgroup analysis of some outcomes for GDM women according to International Association of Diabetes and Pregnancy Study Groups (IADPSG) diagnostic criteria. Method: We searched data through NCBI, Embase, and Web of Science from inception to March 2022. Randomized Controlled Trials (RCTs) were included which compared the outcomes between hypoglycemic agents for GDM women. A Bayes analysis was employed. Results: 29 RCTs were included. The estimated effect of metformin manifested a slight improvement of total gestational weight gain (WMD –1.24 kg, 95% CI -2.38 to -0.09), a risk of unmet treatment target in the sensitivity analysis (OR 34.50, 95%CI 1.18-791.37) than insulin. The estimated effect of metformin showed improvements for birth weight than insulin (WMD – 102.58g, 95% CI -180.45 to -25.49) and glyburide (WMD – 137.84g, 95% CI -255.31 to -25.45), for hypoglycemia within 1 h of birth than insulin (OR 0.65, 95%CI 0.47 to 0.84). The improvement on estimated effect of metformin for hypoglycemia within 1 h of birth still existed when compared with the glyburide (OR 0.41, 95%CI 0.26 to 0.66) whether in the IADPSG group (OR 0.33, 95%CI 0.12 to 0.92) or not (OR 0.43, 95%CI 0.20 to 0.98). Conclusion: Metformin is beneficial for GDM women to control total GWG than insulin, and regulate fetal birth weight than insulin and glyburide, and increase the risk of unmet treatment target than insulin. Glyburide is associated with neonatal hypoglycemia than metformin.